The Silence of the Stakeholders: Zero Decibel Level at Enron - Trinkaus, John (Journal of business ethics, 2005)
While the demise of Enron has raised a number of interesting issues, such as proper governance of large corporations, and the effectiveness and efficiency of statutory direction and regulatory mechanisms, the lack of meaningful vocal stakeholder stewardship has not been one of them. While the relative “silence” of Enron’s stakeholders (watchdogs) could simply have been a communication glitch, or a temporary lapse in social morality, an understanding of hat was not said and why, could well be a significant requisite in formulating meaningful measures to preclude future Enrons., Why weren’t the watchdogs barking? Why had the stakeholder alert system shut down? Further, what are the implications for then and now of this quiescence? Since Enron’s demise many questions have been asked and answered about what went wrong. But little has been said about why the stakeholders failed to speak out by exercising their fiduciary responsibilities. This paper takes a closer look at the behavior of some key Enron stakeholders.